The Urgency of Impostor Phenomenon in Educational Institutions - Mutiara Aqilla Tasya; Juntika Nurihsan; Eka Sakti Yudha; Philein Sophia Putri Dakes; Rifqi Fadhillah Farmadi (Universitas PGRI Yogyakarta, 2024)
The impostor phenomenon is a unique phenomenon that occurs in high achieving individuals. The impostor phenomenon can affect a person's psychological well-being, such as work, academics, interpersonal relationships, or the ability to achieve self-actualization. This research aims to look at the description and urgency of the impostor phenomenon among students. This research uses literature study methods in various journals, book chapters, theses such as Science Direct, Psyc Info, Sage, and Taylor & Francis, and the Online Thesis database. The results of research from 9 selected pieces of literature showed that students often experience the impostor phenomenon in the